The Managerial Study of Pro-Environmental Behavior in Luxury Hotel Industry: An Example of Reducing Disposal Amenities - Yu, Jing; Kasim, Azilah (International Journal of Psychosocial Rehabilitation, 2020)
The appearance of pro-environmental measures has become a manifestation of the global trend in many industries, and hotel management is no exception. The reduction of guest room disposable amenities in hotel operations has seen much improvement and has become more effective in recent years. These are a commonly encountered practical measure toward lower carbon emissions and consist of eco-friendly materials and supplies. However, it is not immediately clear how measures for the promotion of such efforts can be effectively taken by hotel residents. Drawing upon the notion of pro-environmental behavior from the hotel management side, this study investigated the reduction of guest room amenities, its acceptance by guests, and the hotel’s business performance obtained from data provided by luxury hotels in Guangzhou, China. To this end, a two-way ANOVA statistical model was utilized. In addition, this study empirically demonstrated primary results and implications and suggests cost-saving methods for hotel operations.